La desintegración familiar y su influencia en el aprendizaje de los niños/as de 5 años de edad de la I.E N°299 Barrios Altos del distrito de Nueva Cajamarca - Sánchez Aguinaga, María Gladys (2012)
The present work of lnvestigation developed with the aim to determine the influence of the familiar disintegration in the learning of the children ?Jnd fiveyear- old girls of age of the Educational lnitial lnstitution N ° 299 - High Neighborhoods ofthe District of New Cajamarca in the year 2010. The design selected for the present investigation is Causal- Comparatively, for it the population is constituted by 44 five-year-old pupils of age of both sexes of the Level of lnitial Education and the selected sample belonged 17 students between children and girls of equally it forms also 17 parents took part to measure the familiar disintegration. Accused and analyzed the statistical information, we conclude with the following results: 82 % of the parents his home is shaped by his children, 77 % affirmed that it does not coexist with his pair .el 53 % they demonstrated that the problem of the familiar disintegration fu because of infidelities, 65 % affirmed that after the separation they returned to compromise, 47% that opposite to the abandon of his pair, his children feel depression, 76 % demonstrated that after the separation his children never receive affection, 71 % affirmed that after the separation they never visitad his children, 100 % of the parents affirmed they are conscious that the familiar disintegration brings problems in the learning and behavior of his children. The most relevant reasons for which the familias disintegrate are the following ones: the alcoholism, the incompatibility of characters, the lack of communication, and the infidelity like also the physical mistreatment. The children and girls from disintegrated familias are those who present an evil behavior, fall autoestimates and an unfavorable learning.